Using text mining to support text summarization - Reategui, Eliseo; Epstein, Daniel (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2015)
Reading and writing texts are foundational abilities required for daily activities, human interaction and almost all school disciplines. However, it is not uncommon to find students with reading and writing difficulties. Those difficulties interfere on their learning process and their ability to comprehend more complex ideas. Therefore, failing to read and write leads not only to academic failure but it may also hinder occupational success. Several studies have presented graphic organizers as a way to assist students in reading comprehension tasks and to help them structuring their own text production. Here we present a text mining tool capable of extracting the main concepts and relationships from texts present them in a graphical way. These visual representations of a text may be used by students as graphic organizers, helping them to reflect about the text’s main ideas before the actual writing task. The results of an experiment are presented, in which a total of 20 students were asked to read and summarize a short text with the assistance of the text mining tool. The results show that Sobek helped students reflect about the main ideas of the text and supported the actual writing of the summaries.